RETRACTED: Analysis of disease burden and future trends of ischemic heart disease in China and globally, 1990–2023 - Zhuo Zhang; Guihua Yue; Longlong Wang (PLoS ONE, 2025)
Background This study aimed to analyze the characteristics and trends of the disease burden of ischemic heart disease (IHD) in China and worldwide, across different age and sex groups, to provide a comprehensive understanding of the situation in China. Methods Using GBD 2023 data, we analyzed global and China-specific IHD incidence, prevalence, mortality, and DALYs. Joinpoint regression was used to assess trends, while factors such as aging and population growth were also examined. An ARIMA model projected the IHD burden from 2024 to 2050. Results From 1990 to 2023, the age-standardized incidence rate (ASIR) and prevalence rate (ASPR) of IHD in China exhibited an upward trend. The ASIR per 100,000 increased from 109.7 (95% uncertainty interval [UI]: 93–128) to 110.3 (95% UI: 89–131), while the age-standardized mortality rate (ASMR) decreased from 126.8 (95% UI: 92–163) to 109.5 (95% UI: 94–127), mirroring global trends. The highest incidence of IHD was observed in individuals aged 60–89 years, with mortality peaking between 80–89 years. AAPC analysis revealed that China’s ASIR (AAPC = −0.091%; 95% CI: −0.152 to −0.029) and ASPR (AAPC = 0.227%; 95% CI: 0.115 to 0.34) increased more rapidly than the global average. Decomposition analysis indicated that the rise in IHD burden in China was primarily driven by population aging and growth, a pattern observed globally. Forecasting models suggest that the ASIR will continue to rise in China through 2050, while the ASMR and age-standardized DALYs rates (ASDR) are expected to decline further. Conclusion The incidence and prevalence of IHD in China are projected to rise through approximately 2030. Older males bear a disproportionate burden of the disease. More targeted preventive, diagnostic, and therapeutic strategies are urgently needed and should be informed by the findings of this study.